Methanol in the RNA world: An astrochemical perspective - Mathew, Thomas; Esteves, Pierre Mothé; Prakash, G. K. Surya (Frontiers in Astronomy and Space Sciences, 2022)
Role and Relevance of methanol in the origin and structure of RNA world is discussed. Methanol is pivotal, renewable and regenerable source from which almost all chemical materials, simple or complex can be accessed. Olefins and carbonyl compounds, amines and amino acids, peptides and polypeptides, the molecular building blocks in the initial stage of biological evolution to life’s origin are obtained through methanol as a source material by its chemical transformation. Formation of methanol, whether it is in stellar and interstellar medium, in deep sea-bottom hot hydrothermal vents or from geothermal sources, results from CO2 hydrogenation. It is the basic reaction, setting stage for the formation of fundamental “organic” building blocks for the formation of simple prebiotic cells to subsequent biological evolution to cells. The important observation of many organics-hydrocarbons and ions including large expanse of methane and methanol in interstellar medium and stellar peripheries is a clear indication of “stellar reductive processes” and ensuing reactions shedding light on the probable significant role of extraterrestrial methanol as the basic source material towards in a multi-step transformation into complex life molecules such as RNA.